Evolution Of Helical Screw Pile Design And Installation - Michael Perlow (Deep Foundations Institute, 2011)
Helical screw piles in use since 1838 are routinely used for energy, transportation, municipal, industrial, marine and coastal infrastructure as well as for excavation support, environmental remediation, and foundation repair. They are especially well suited for work in constrained areas, renovations and structure retrofits. Helical pile design procedures over the past 10 years have gone through a remarkable evolution with the establishment of the 2007 AC358 Helical Pile Acceptance Criteria and inclusion of helical screw piles in the 2009 International Building Code (IBC). New 2009 IBC building code requirements and AC358 Acceptance Criteria are presented along with advances in helical pile design procedures, installation, QA/QC, and recommended load test verification criteria. Use of helical smart piles to validate helical pile design and verification of ultimate pile capacity is highlighted.